Cinnamaldehyde inactivates Listeria monocytogenes at a low temperature in ground pork by disturbing the expression of stress regulatory genes. (February 2023) - Guan, Peng; Wang, Xiaojie; Dong, Zijie; Song, Miao; Zhu, Hongshuai; Suo, Biao
Abstract: Listeria monocytogenes is a cold tolerant foodborne pathogen that frequently detected in ground pork stored at low temperature. The study firstly evaluated the inhibitory effect of cinnamaldehyde on Listeria monocytogenes at 4°C and the mechanism by which cinnamaldehyde interferes with the adaptive gene regulation system. When low temperature and cinnamaldehyde were combined for treating L. monocytogenes, the time required to cause a reduction by 2 log CFU/g ( t 2.0 ) was decreased along with the increase of cinnamaldehyde concentration, although cinnamaldehyde may produce an unpleasant but acceptable odor. Transmission electron microscopy (TEM) results showed severe rupture of the cell envelope and leakage of cytoplasmic contents in cells treated with a combination treatment of cinnamaldehyde and low temperature, but the effect of individual treatment is not obvious. Real-time quantitative PCR results revealed that the stress resistance genes ( gbuA, gbuB, gadD2, groEL, rli60 and ilvD ), regulatory genes ( prfA, sigB, codY and luxS ) and cold shock response genes ( cspA, cspB and cspD ) were actively involved in the response to the low temperature. However, the combination of cinnamaldehyde and low temperature treatment disturb the gene regulation. Molecular docking results further indicate that cinnamaldehyde may interact with protein PrfA and LuxS amino acid residues through hydrogen bonding, thus interfering with regulator activity. The results firstly indicates that cinnamaldehyde has a synergistic inhibition effect on L. monocytogenes in cold stored ground pork by rupturing cell envelop and disturbing stress regulatory gene expression, which provides a new idea for the safety control of chilled meat. Highlights: The antibacterial effect of cinnamaldehyde on L. monocytogenes at 4 °C was firstly evaluated. Cinnamaldehyde has strong antibacterial effect on L. monocytogenes in cold stored ground pork. The Weibull model successfully predicted the inactivation of L. monocytogenes . Cinnamaldehyde interferes with stress regulatory gene expression in L. monocytogenes at 4 °C. Molecular docking analysis shows cinnamaldehyde bind to regulatory factors.